Long-term follow-up of papillary and follicular thyroid carcinomas with bone metastasis - Lin, Jen-Der (PLoS One, 2017)
The aims of this study were to investigate papillary and follicular thyroid carcinomas with bone metastasis in various clinical presentations and to determine the prognostic factors after multimodality treatment. A retrospective analysis was performed of 3,120 patients with papillary and follicular thyroid carcinoma. Of these patients, 131 (including 97 women, 71.8%) were diagnosed with bone metastasis and underwent follow-up at the Chang Gung Medical Center. Patients with bone metastasis were categorized into two groups. Group A was comprised of patients who were diagnosed with bone metastasis either before thyroidectomy or within 6 months of the initial thyroidectomy (90 patients, 68.7%). Group B was comprised of patients with bone metastasis who received a diagnosis 6 months post-thyroidectomy in the follow-up period (41 patients, 31.3%). After a mean follow-up period of 8.4 ± 7.0 years, there were 88 deaths (67.2%) attributed to thyroid cancer and 13 patients (9.9%) achieved disease-free status. A multivariate analysis showed that older age, early diagnosis, and brain metastasis were each associated with a poor prognosis. The difference in disease-specific mortality rates between groups A and B was significant (p < 0.0001). In conclusion, papillary and follicular thyroid cancers with bone metastasis have a high rate of mortality. Despite this high mortality, 9.9% patients still had an excellent response to treatment.